Some considerations regarding weather and natural disasters risk management in agriculture sector - Mirela Matei; Ioan Done (Ekonomika Poljoprivrede (1979), 2010)
The literature offers multiple examples regarding the failure of traditional insurance schemes to provide affordable and comprehensible crop insurance (Vedenov, Barnett, 2004). For this reason, in that paper, we have analyzed the development of new financial instruments that permit the securitization of weather and catastrophe risk and erase the limitations of traditional insurance products. The weather derivatives and cat-linked securities are new instruments that determine the transfer of weather and natural disasters risk to a country to international capital market. The interest of individual and institutional investors for these securities is high because of the low correlation with other financial instruments. The development of weather risk market is important for farmers and companies from developing countries but also for investors from developed countries that can diversificate their portfolios.